Pharmaceutical Suspensions: An Updated Patent Review on Novel Suspending Agents and Recent Advancement - Kumar, Prince; Verma, Madhu (Recent Advances in Drug Delivery and Formulation, 2023)
A wide variety of dosage forms are used for the oral administration of drugs to humans and animals. Apart from solid dosage forms, it also includes liquid dosage forms, such as solutions, suspensions, and emulsions. The selection is based on the physiochemical attributes of the therapeutically active ingredient. Suspensions are classified as dispersed systems that are heterogeneous in nature and consist of two phases. One phase is the continuous phase, the dispersion medium, or the external phase, which is either liquid or semisolid; the other is a solid particle dispersed in the external phase and called an internal or dispersed phase. They have several advantages over other dosage forms, such as effectively delivering hydrophobic drugs, avoiding the need for cosolvents, masking unpleasant tastes, and providing resistance to degradation and easy swallowing for young or elderly patients. They also attain higher drug concentrations compared to solution forms. This review article aims to study and explore the advantages, novel suspending agents, patent preference, and innovations of pharmaceutical suspension. It was targeted to scrutinize the literature floating in the internet domain regarding pharmaceutical suspension for delivery of drugs by oral route. The literature survey is targeted at the novel herbal suspending agents used, their patents involved, and innovations in the dosage form. Further, the study gives an insight into various aspects of suspension, such as classification of suspension, theories of suspension, various components used in suspension formulation, formulation aspect of suspension, evaluation parameters of suspension, patents, innovations, and regulatory status.
Keywords: Innovations